2009
DOI: 10.1086/597395
|View full text |Cite
|
Sign up to set email alerts
|

Empirical versus Preemptive Antifungal Therapy for High‐Risk, Febrile, Neutropenic Patients: A Randomized, Controlled Trial

Abstract: Preemptive treatment increased the incidence of invasive fungal disease, without increasing mortality, and decreased the costs of antifungal drugs. Empirical treatment may provide better survival rates for patients receiving induction chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
299
3
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(331 citation statements)
references
References 28 publications
5
299
3
15
Order By: Relevance
“…These patients are admitted to the hospital during their period at high risk, and GM monitoring is recommended every 3-4 days. 11,12 A diagnosis-driven strategy that incorporates prospective GM monitoring should be combined with highresolution computed tomography imaging, and appropriate clinical and microbiological evaluation. 11,12 A single positive GM index of X0.7 or two consecutive samples of X0.5 should prompt a diagnostic work-up.…”
Section: Galactomannan (Gm)mentioning
confidence: 99%
See 1 more Smart Citation
“…These patients are admitted to the hospital during their period at high risk, and GM monitoring is recommended every 3-4 days. 11,12 A diagnosis-driven strategy that incorporates prospective GM monitoring should be combined with highresolution computed tomography imaging, and appropriate clinical and microbiological evaluation. 11,12 A single positive GM index of X0.7 or two consecutive samples of X0.5 should prompt a diagnostic work-up.…”
Section: Galactomannan (Gm)mentioning
confidence: 99%
“…11,12 A diagnosis-driven strategy that incorporates prospective GM monitoring should be combined with highresolution computed tomography imaging, and appropriate clinical and microbiological evaluation. 11,12 A single positive GM index of X0.7 or two consecutive samples of X0.5 should prompt a diagnostic work-up. 13 GM monitoring can be continued after antifungal therapy has been initiated.…”
Section: Galactomannan (Gm)mentioning
confidence: 99%
“…A pilot trial showed a substantial decrease in the use of antifungal drugs compared with the empiric strategy [18]. More recently, a randomized, prospective trial comparing pre-emptive and empiric strategies, mostly in patients with acute leukemia and neutropenia, showed that the former strategy led to increased diagnosis of IFI, no increased mortality, and decreased antifungal drug cost [19]. Again, as with empiric therapy, data on preemptive strategy in HSCT recipients, although much needed, are not available.…”
Section: Pre-emptive Therapymentioning
confidence: 99%
“…Since then, there have been several randomized, controlled trials comparing empiric to the preemptive approach, but heterogeneity in study designs makes interpretation of the results challenging (Table 2). [80][81][82] As such, the safety and efficacy of replacing empiric with preemptive antifungal therapy in neutropenic patients have not been established; additional prospective studies are needed. Also, the finding that posaconazole causes the serum GM surveillance of asymptomatic patients to be unreliable brings the relevancy of the preemptive strategy into question at those centers that routinely employ effective anti-mold prophylaxis.…”
Section: Improving Diagnosis Of Invasive Aspergillosismentioning
confidence: 99%